Contribution Of Madrasah In Enhancing Curiculum 2013 (A Study On The Readiness Of Madrasah In Implementing Of Curiculum 2013 In Central Java) - Mulyani Mudis Taruna (Analisa: Journal of Social Science and Religion, 2015)
This study aimed to describe the implementation of Curriculum 2013 in Madrasa tsanawiyah (MTs). The preparation includes readiness head MTs, the readiness of teachers, as well as enabling and inhibiting factors in the implementation of Curriculum 2013 MTs. The subjects of this study were MTs in Central Java. This study used a qualitative method with the following results; (1) generally head MTs and subject teachers at the school has been able to implement the K-13, both from the aspect of the facility and in the course of learning in the classroom. (2) supporting factor in the implementation of the curriculum in 2013 at MTs, including the existence of a workshop K-13 by the schools and by the working group of Madrasah (KKM), while inhibiting factor in the implementation of the curriculum in 2013 was the absence of mentoring supervisor madrassas and no handbook of teachers and learners, especially on the subjects of religious education.